Role of Neutrophil Apoptosis in the Resolution of Inflammation - Driss El Kebir; János G. Filep (The Scientific World Journal)
Neutrophil granulocytes play a central role in host defense to infection and tissue injury. Their timely removal is essential for resolution of inflammation. Increasing evidence identified neutrophil apoptosis as an important control point in the development and resolution of inflammation. Delayed apoptosis and/or impaired clearance of neutrophils aggravate and prolong tissue injury. This review will focus on outside-in signals that provide survival cues for neutrophils, the hierarchy of pro- and antiapoptotic signals, and molecular targets in the antiapoptotic signaling network that can be exploited by endogenously produced bioactive lipids, such as lipoxins or pharmacological inhibitors, including cyclin-dependent kinase inhibitors, to redirect neutrophils to apoptosis in vivo, thus promoting resolution of inflammation.